Psychometric Properties of the “Quality of Life in Life-Threatening Illness—Family Carer Version” (QOLLTI-F) in Persian-Speaking Carers of COVID-19 Patients - Fereidouni, Armin; Ebadi, Abbas; Rassouli, Maryam; Hosseini, Seyed Morteza; Mollahadi, Mohsen; Khorshidvand, Ali; Javid, Mohammad; Ansari, Behnam; Rezaei, Mohammad Saeid; Barasteh, Salman (Frontiers in Psychology, 2022)
Abstract Background: Measuring family caregivers’ quality of life plays a significant role in improving the quality, efficiency, development, and provision of efficient services for patients with COVID-19. As a result, evaluating the quality of life requires the use of valid and reliable measures that are culturally appropriate. This study was conducted to determine the psychometric properties of the Persian version of the Quality of Life in Life-Threatening Illness–Family Carer Version (QOLLTI - F) in patients with COVID-19. Methods: This methodological study was carried out in 2021 at Baqiyatallah Hospital in Tehran. After gaining approval from the tool creator, the translation was carried out utilizing the forward-backward approach. Cognitive interviews with 10 family caregivers of COVID-19 patients were used to demonstrate face validity. Moreover, construct validity was identified by performing exploratory factor analysis (n = 251), confirmatory factor analysis (n = 200), and convergent validation using Zarit Burden Interview questionnaire. For scale reliability, internal consistency and stability were performed using Cronbach’s Alpha Coefficient and test-retest, respectively. Results: 451 family caregivers of patients with COVID-19 were enrolled in this study. Three factors with a cumulative variance of 51.85% were extracted during exploratory factor analysis: 1. Caregiver’s physical-emotional status 2. Satisfaction with the situation 3. Caregiver’s concerns. Confirmatory factor analysis showed that the model enjoyed a moderate to a good fit of information. (RMSEA: 0.087; NFI: 0.98; CFI: 0.91; IFI: 0.91; GFI 0.89; standardized RMR: 0.070). A significant correlation was found between the Persian version of the Zarit Burden Interview and participants’ total scores of QOLLTI – F v3 (r = -0.196, P = 0.000). Cronbach’s Alpha Coefficient= 0.719 and ICC stability reliability = 0.71 of the questionnaire were confirmed. Conclusion: The Persian version of the QOLLTI - F v3 is a valid and reliable scale that can measure family caregivers’ quality of life during a Life-Threatening illness in patients with COVID-19. This instrument may be utilized in clinical trials and research to enhance the quality of life for family carers in Iranian society.